(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article examines the issues of assessing the nutritional status of prisoners and its significance from a scientific and analytical perspective. It proves that nutrition is one of the important factors determining the health of a person, including a person in a penal institution, and that proper nutrition in accordance with the procedure established by regulatory documents is one of the important measures aimed at preventing the spread of infectious diseases not only among prisoners, but also among the entire population.